Postdisaster Social Capital, Adaptive Resilience and Business Performance of Tourism Organizations in Christchurch, New Zealand. (September 2019) - Chowdhury, Mesbahuddin; Prayag, Girish; Orchiston, Caroline; Spector, Samuel
The resilience of tourism organizations is an important issue for destinations. While studies examine the social capital of firms, researchers have yet to understand the relationship between social capital (structural, relational and cognitive) and organizational resilience as predictors of business performance. This study evaluates these relationships at the interfirm level among tourism organizations in the postdisaster context of Christchurch, New Zealand, where business performance for some tourism operations was severely impacted. Surveys of tourism organizations reveal that structural capital has a positive relationship with both cognitive and relational capital. Only relational capital has an influence on adaptive resilience. Adaptive resilience has a significant influence on business performance. By showing which elements of social capital contribute to adaptive resilience, these findings can be used by tourism organizations in their recovery phase to direct investments in building resilience and strengthening interfirm relationships.